Synthesis, characterization and X-ray structures of 2,6-diacetylpyridinebis(benzenesulfonylhydrazide) and its zinc(II) complex - Yusnita, J.; Ali, Hapipah Mohd; Robinson, W.T.; Abdulla, M.A.; Puvaneswary, S. (2009)
2,6-Diacetylpyridinebis(benzenesulfonylhydrazide) (2,6-DAPBSH) and its zinc(II) complex have been synthesized and characterized by X-ray crystallography. The ligand crystallizes in the monoclinic crystal system, space group Cc, with cell parameter = 16.808(2) angstrom, b = 16.328(2) angstrom, c = 8.2670(11) angstrom, beta = 91.869(9)degrees, while the zinc( II) complex crystallizes in the orthorhombic crystal system, space group Pbcn, with cell parameters a = 14.5927(3) angstrom, b = 9.6502(2) angstrom, c = 20.5610(5) angstrom. The metal center is seven-coordinate, with an approximate pentagonal bipyramidal configuration of the chelating ligand and two apically coordinated DMSO molecules.